2018
DOI: 10.1111/jth.13898
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS‐13 and von Willebrand factor: a dynamic duo

Abstract: Summaryvon Willebrand factor (VWF) is a key player in hemostasis, acting as a carrier for factor VIII and capturing platelets at sites of vascular damage. To capture platelets, it must undergo conformational changes, both within its A1 domain and at the macromolecular level through A2 domain unfolding. Its size and this function are regulated by the metalloproteinase ADAMTS‐13. Recently, it has been shown that ADAMTS‐13 undergoes a conformational change upon interaction with VWF, and that this enhances its act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 114 publications
2
51
0
6
Order By: Relevance
“…Based on these data, further work was performed to explore the mechanistic roles of inflammation and endothelial dysfunction in mediating chorioretinal changes. Plasma von Willebrand factor (vWF; an endothelial activation marker) [ 15 ] and endothelin-1 (ET-1; an endogenous vasoconstrictor strongly linked with endothelial dysfunction) [ 16 ] were measured. Both vWF and ET-1 were markedly elevated before OLT, correlating significantly with severity of liver disease (MELD and variceal staging) and decreased substantially when rechecked 6 weeks after transplantation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these data, further work was performed to explore the mechanistic roles of inflammation and endothelial dysfunction in mediating chorioretinal changes. Plasma von Willebrand factor (vWF; an endothelial activation marker) [ 15 ] and endothelin-1 (ET-1; an endogenous vasoconstrictor strongly linked with endothelial dysfunction) [ 16 ] were measured. Both vWF and ET-1 were markedly elevated before OLT, correlating significantly with severity of liver disease (MELD and variceal staging) and decreased substantially when rechecked 6 weeks after transplantation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…ADAMTS13 cleaves the cryptic peptide bond Tyr1605-Met1606 in VWF-A2 domain converting the prothrombotic ULVWF to smaller and less adhesive multimers, preventing aberrant platelet aggregation and thrombus[28, 29]. Deficiency of ADAMTS13 activity resulting from hereditary or acquired etiologies results in TTP[5, 29]. It has been shown that ADAMTS13 adopts a “closed” conformation through the interaction between the spacer and CUB domains[13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological balance of VWF levels is highly regulated through its expression, storage and release in one hand, and clearance on the other hand . If this balance is disturbed in favor of sustained increased levels of VWF, as in TTP, it leads to significant undesired thrombogenicity . The potential for VWF association with increased thrombogenicity is clearly consistent with its role as a mediator of platelet aggregate formation, which is the first and central step in thrombus formation .…”
Section: Introductionmentioning
confidence: 92%